A Cognitive Journey for Requirements Engineering. Issue 1 (13th September 2016) - Feldman, Yishai A.; Broodney, Henry
Abstract: The classical systems engineering practice is mostly process centric, but with the recent advances in Information Technologies, we have started to engage in model‐based and other software‐supported activities that make us more efficient and our products better. The subject of this paper is a pursuit of further improvements in the software tools supporting the systems engineers, this time an attempt to transform the regular textual requirements into computer‐readable artifacts that will enable software tools to better analyze a requirement set and to automate cross‐lifecycle exchange of information leading to increased automation and higher quality. The paper starts by describing an experiment targeted at requirements formalization, continues with the insights gained from the experiment, and finishes with the insights1 that the authors have reached on a reasonable and incremental roadmap to a fully synergetic interaction between Requirements Engineers and their supporting tools.